2015
DOI: 10.3109/00498254.2015.1026864
|View full text |Cite
|
Sign up to set email alerts
|

Human mass balance, metabolite profile and identification of metabolic enzymes of [14C]ASP015K, a novel oral janus kinase inhibitor

Abstract: 1. The human mass balance of (14)C-labelled ASP015K ([(14)C]ASP015K), an orally bioavailable Janus kinase (JAK) inhibitor, was characterized in six healthy male subjects after a single oral dose of [(14)C]ASP015K (100 mg, 3.7 MBq) in solution. [(14)C]ASP015K was rapidly absorbed with tmax of 1.6 and 1.8 h for ASP015K and total radioactivity in plasma, respectively. Mean recovery in urine and feces amounted to 36.8% and 56.6% of the administered dose, respectively. The main components of radioactivity in plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 16 publications
1
31
0
Order By: Relevance
“…The higher drug exposure in Japanese subjects is consistent with observations in a previous study, in which peficitinib C max and AUC were found to be higher in Asian subjects compared with non-Asian subjects [20]. Peficitinib is metabolized by the sulfotransferase (SULT) isoenzyme, SULT2A1, and the methyltransferase isoenzyme, nicotinamide N-methyltransferase [18]. To date no genetic polymorphisms of these isoenzymes have been reported, and the cause of higher peficitinib exposure in Asian patients remains unknown.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The higher drug exposure in Japanese subjects is consistent with observations in a previous study, in which peficitinib C max and AUC were found to be higher in Asian subjects compared with non-Asian subjects [20]. Peficitinib is metabolized by the sulfotransferase (SULT) isoenzyme, SULT2A1, and the methyltransferase isoenzyme, nicotinamide N-methyltransferase [18]. To date no genetic polymorphisms of these isoenzymes have been reported, and the cause of higher peficitinib exposure in Asian patients remains unknown.…”
Section: Discussionsupporting
confidence: 89%
“…Plasma and urine samples were stored at − 70 °C and were sent to BML, Inc. Central Laboratory (Saitama, Japan) for analysis of peficitinib concentrations. Peficitinib concentrations in plasma and urine were measured using a validated liquid chromatography with tandem mass spectrometry method [18]. The lower limits of quantification for peficitinib in plasma and urine were 0.25 ng/mL and 2.5 ng/ mL, respectively.…”
Section: Pharmacokinetic Assessmentsmentioning
confidence: 99%
“…The concentrations of plasma peficitinib and H2 metabolite (sulfate metabolite, equivalent to M2 identified previously [18]) were measured using validated liquid chromatography tandem mass spectrometry (LC-MS/MS). The lower limit of quantification (LLOQ) was 0.25 ng/mL when 25 μL of plasma was used.…”
Section: Peficitinib and Metabolite H2 (M2)mentioning
confidence: 99%
“…16 PK parameters were determined using noncompartmental analysis of plasma concentration-versus-time data using WinNonlin-Professional, version 5.3 (Pharsight Corporation, Mountain View, California). Urine samples were collected predose (ࣘ30 minutes) on day 1 and from 0 to 6, 6 to 12, 12 to 24, 24 to 48, and 48 to 72 hours postdose.…”
Section: Pharmacokinetic Analysismentioning
confidence: 99%
“…Plasma and urine ASP015K concentrations were determined using a validated liquid chromatography-tandem mass spectrometry method. 16 PK parameters were determined using noncompartmental analysis of plasma concentration-versus-time data using WinNonlin-Professional, version 5.3 (Pharsight Corporation, Mountain View, California). All concentrations that were below the limit of quantitation were set to zero prior to computation of arithmetic means.…”
Section: Pharmacokinetic Analysismentioning
confidence: 99%